Clinical evaluation of total and lipid bound sialic acid levels in oral precancer and oral cancer - Syed Ahmed Taqi (Indian Journal of Medical and Paediatric Oncology)
Aims: Special attention has been given to define the biochemical changes in cell-surface glycoproteins and glycolipids that take place during malignant transformation. This study was thus designed to explore the clinical utility of total and lipid bound sialic acid (LSA) in patients with oral precancer and oral cancer. Materials and Methods: Blood samples were obtained from 95 subjects divided into three groups, namely healthy individuals, oral cancer, and precancer. Serum total and LSA levels were determined using periodate-thiobarbituric acid method and Katopodis et al. method, respectively. Finally, spectrophotometricreadings were obtained. Results: Mean values of serum sialic acid (total and lipid bound) in oral cancer were significantly higher than control and the precancer group (P<0.001). The multivariate analysis data revealed progressive rise in total and LSA, which was statistically significant with clinical stage of the cancer. Conclusion: Serum sialic acid levels can differentiate between patients with oral precancer and oral cancer. It could be used as an adjunct to diagnosis, monitor response to therapy, and assess the staging of cancer.